Web-age information management : WAIM 2011 International Workshops: WGIM 2011, XMLDM 2011, SNA 2011, Wuhan, China, September 14-16, 2011, Revised Selected Papers - Wang, Liwei (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of three workshops of the 12th International Conference on Web-Age Information Management, WAIM 2011, held in Wuhan, China, in September 2011. The 20 revised full papers are organized in topical sections on the three following workshops: the First International Workshop on Web-based Geographic Information Management (WGIM 2011), the Third International Workshop on XML Data Management (XMLDM 2011), and the First International Workshop on Social Network Analysis (SNA 2011).